2021
DOI: 10.3390/ijms22073614
|View full text |Cite
|
Sign up to set email alerts
|

Atractylodin Produces Antinociceptive Effect through a Long-Lasting TRPA1 Channel Activation

Abstract: Atractylodin (ATR) is a bioactive component found in dried rhizomes of Atractylodes lancea (AL) De Candolle. Although AL has accumulated empirical evidence for the treatment of pain, the molecular mechanism underlying the anti-pain effect of ATR remains unclear. In this study, we found that ATR increases transient receptor potential ankyrin-1 (TRPA1) single-channel activity in hTRPA1 expressing HEK293 cells. A bath application of ATR produced a long-lasting calcium response, and the response was completely dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Chemical activation of TRPA1-expressing nociceptors produces an intense burning pain sensation, 55 with TRPA1-knockout mice lacking sensitivity to AITC. 56 , 57 This pain induction model has been previously shown, using observer-dependent assays, to induce peak acute nociception within the first 3 mins postinjection, manifesting itself with increased licking of the injected footpad 58 ; mechanical hypersensitivity can also persist after injection for over an hour. 59 This was consistent with our findings that showed consistently decreased ipsilateral paw weight in the AITC group compared to controls over 5 mins after injection, with the greatest effect evident during the first minute after injection (see Figure 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…Chemical activation of TRPA1-expressing nociceptors produces an intense burning pain sensation, 55 with TRPA1-knockout mice lacking sensitivity to AITC. 56 , 57 This pain induction model has been previously shown, using observer-dependent assays, to induce peak acute nociception within the first 3 mins postinjection, manifesting itself with increased licking of the injected footpad 58 ; mechanical hypersensitivity can also persist after injection for over an hour. 59 This was consistent with our findings that showed consistently decreased ipsilateral paw weight in the AITC group compared to controls over 5 mins after injection, with the greatest effect evident during the first minute after injection (see Figure 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…Study evidence shows that injection of QX-314 (lidocaine derivative) together with capsaicin into rat hind paws produces a long-lasting mechanical and thermal nociceptive threshold. Also, regional injection of QX-314 and capsaicin near the sciatic nerve produces a long-lasting decrease in pain sensitivity [ 33 ]. Monteiro de Araujo et al, reviewed existing literature on the role of pharmacological interventions on TRPA1 to reduce pain in numerous pain conditions and concluded that TRPA1 may be a therapeutic target for nociceptive pain [ 34 ].…”
Section: Discussionmentioning
confidence: 99%